Large electrocaloric effect with ultrawide temperature span in Na1/2Bi1/2TiO3‐based lead‐free ceramics. Issue 5 (5th January 2022) - Wei, Qiumei; Fulanovic, Lovro; Lalitha, Kodumudi Venkataraman; Zheng, Mupeng; Hou, Yudong; Zhu, Mankang; Liu, Linjing; Chang, Yunfei; Xue, Rui
Abstract: Innovative cooling technologies are recognized by many industries as a crucial part of their system design. A large electrocaloric effect (ECE) and extended working temperature are the key issues hindering the realization of electrocaloric refrigeration technology. In this work, large ECE (Δ T = 0.8–0.9°C @ 4 kV/mm) with an ultrawide temperature span from 30 to 120°C is noted for lead‐free (Na1/2 Bi1/2 )0.80 Sr0.20 (Zn1/3 Nb2/3 ) x Ti1‐ x O3 ceramics. The excellent ECE performance can be ascribed to the evolution of polar nanoregions. Our work suggests that this material is promising for applications in solid‐state refrigeration systems with a broad range of operating temperatures.